The bigger bang - Lidsey, James E., 1967- (Canto (Cambridge University Press), 2002)
In the last few years, scientists have begun to answer some of the most fundamental questions about the origin and early evolution of the universe. This book presents a fresh and engaging introduction to these ideas. Lucid analogies and clear and concise language make this book a delight to read.